2021
DOI: 10.1002/ente.202100164
|View full text |Cite
|
Sign up to set email alerts
|

The 2‐Propanol Fuel Cell: A Review from the Perspective of a Hydrogen Energy Economy

Abstract: The 2‐propanol fuel cell has been shown to hold several key advantages over the more established methanol fuel cell, including a comparably high real open‐circuit voltage, reduced fuel crossover through a Nafion membrane and a benign toxicological fuel profile. In addition, while the highly selective partial oxidation of 2‐propanol to acetone in a fuel cell (rather than the more typical complete combustion of organic fuels to CO2) has been viewed as a disadvantage in the past, recent work has shown that the 2‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 87 publications
(191 reference statements)
0
46
0
Order By: Relevance
“…In the literature, a 2 m aqueous solution is recommended as higher 2‐propanol concentrations lead to damage of the MEA with current membrane material. [ 3 ] In heat exchanger 1, the 2‐propanol‐water solution is heated but not evaporated. The heat can be recovered from the exhaust gas stream or the cooling system that transfers the waste heat from the fuel cell.…”
Section: Results and Discussion Of Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, a 2 m aqueous solution is recommended as higher 2‐propanol concentrations lead to damage of the MEA with current membrane material. [ 3 ] In heat exchanger 1, the 2‐propanol‐water solution is heated but not evaporated. The heat can be recovered from the exhaust gas stream or the cooling system that transfers the waste heat from the fuel cell.…”
Section: Results and Discussion Of Scenariosmentioning
confidence: 99%
“…[ 2 ] Instead, it has been found that secondary alcohols, such as 2‐propanol, are attractive fuels for direct electrification. [ 3 ] Most interestingly, the dehydrogenation of 2‐propanol in a proton exchange membrane (PEM) fuel cell setup stops at acetone and no CO 2 is formed. [ 4 ] The resulting acetone can be recharged with hydrogen via catalytic hydrogenation [ 5 ] or transfer hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 49,63 ] In addition, the use of isopropanol produces acetone without other byproducts; however, the research on direct i‐ PrOH fuel cell (DIFC) is still at its earlier stage and require much efforts in the improvement of devices architectures. [ 63a ]…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, the employment of isopropanol as hydrogen energy carrier has attracting increasing interest avoiding the energy costs issues related to the dehydrogenation pathway of other LOHCs (i.e., perhydro dibenzyltoluene). [ 49,63 ] In addition, the use of isopropanol produces acetone without other byproducts; however, the research on direct i‐ PrOH fuel cell (DIFC) is still at its earlier stage and require much efforts in the improvement of devices architectures. [ 63a ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation